Analisis Risiko Dan Arus Kas Terhadap IRR : Studi kasus pada PT. Dharmala Intiland Tbk, PT. Duta Pertiwi Tbk dan PT. Kawasan Industri Jababeka Tbk - Hidayat, Lukman; Mhaydali, Shana (Jurnal Ilmiah Ranggagading (JIR), 2008)
This research is intended to learn of companies finance condition, namely concerning risk, cash flow, and companies IRR. The researchers do this research indirectly outside of the companies to get data of the companies from BEJ in care of internet site. Based on the result of this research, it can be concluded that finance condition of PT Dharmala Intiland Tbk., from risk point of view, is low enough because the company has just little investment so that it has no high risk. From cash flow point of view, PT Dharmala Intiland bk. can be said as good because even though it got decrease in several years, but in several years after that, it got significant increase. The companys IRR can be said good as well because its IRR is more than RRR. From risk point of view, PT Duta Pertiwi Tbk. Can be said low enough because the company has just little investment so that it can manage risk management to minimize its risk. From cash flow point of view, the company is good enough as well even though it got little decrease in several years but years later it got increase. From IRR point of view, the company is very good because its IRR got much higher than its RRR. PT Kawasan Industri Jababeka Tbk. Has high risk enough because the company has high investment. This matter jeapordizes the company condition. From cash flow point of view, PT Kawasan Industri Jababeka Tbk. Is not so good because it fluctuates and decreases year by year, likewise its IRR is lower than RRR. The companys finance condition is influenced by the companys performance. Keywords: Deviation standard; Variation coefficient; Cash flow; IRR